PENGGUNAAN MEDIA KAHOOT.IT SEBAGAI ENRICHMENT KEMAMPUAN BERPIKIR KREATIF MAHASISWA MATA KULIAH KONSEP DASAR IPS - Sri Mulyati (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2020)
AbstractThe background of this research is a minimal learning process that is supported bystudents' creativity and learning to take advantage of internet technology, a specialapplication of E-Learning as a medium for learning in the classroom. The purpose ofthis paper is to describe the use of the kahoot.it application in lectures on the basicconcepts of social studies that discuss integrated economics, geography, history andsociology. The success of this learning media is expected to be one of the solutions toimprove students' thinking abilities and also be able to improve social studies that aredifficult, rigid, monotonous, unattractive, and so on. Basically the use of kahoot.itlearning media in learning is an online evaluation tool for enrichment in class. Theresearch method used is qualitative with the objectives obtained using the mediakahoot.it in class. The use of instructional media does not only focus on specific learningmethods, but can be combined with any learning method that is tailored to thecharacteristics of students.Keywords: kahoot.it; social studies learning; and think creatively.